Congenital cervical teratoma mimicking as neuroblastoma on cytology: A diagnostic pitfall - Sahil Chhabra; Harshi Dhingra; Asif Baliyan; Amarjit Singh; Vijay Suri (Indian Journal of Medical and Paediatric Oncology)
Cervical teratomas are very rare tumors, accounting for approximately 3%–5% of all pediatric teratomas with predominance in females. Most common site of cervical teratoma is sacrococcygeal region and occurrence in cervical region is a rare presentation. We present a case of cervical teratoma in a 4-month-old male infant presenting as neck mass mimicking as neuroblastoma with differentiation on fine-needle aspiration. The final diagnosis of mature teratoma was made on histopathological examination.